Radioactive cesium concentrations in coastal suspended matter after the Fukushima nuclear accident. (June 2018) - Kubo, Atsushi; Tanabe, Kai; Suzuki, Genta; Ito, Yukari; Ishimaru, Takashi; Kasamatsu-Takasawa, Nobue; Tsumune, Daisuke; Mizuno, Takuji; Watanabe, Yutaka W.; Arakawa, Hisayuki; Kanda, Jota
Abstract: Radioactive cesium concentrations in the suspended matter of the coastal waters around the Fukushima Daiichi Nuclear Power Plant (FDNPP) were investigated between January 2014 and August 2015. The concentrations of radioactive cesium in the suspended matter were two orders higher in magnitude than those determined in the sediment. In addition, we discovered highly radioactive Cs particles in the suspended matter using autoradiography. The geometrical average radioactivity of particles was estimated to be 0.6 Bq at maximum and 0.2 Bq on average. The contribution ratio of highly radioactive Cs particles to each sample ranged from 13 to 54%, and was 36% on average. A major part of the radioactive Cs concentration in the suspended matter around the FDNPP was strongly influenced by the highly radioactive particles. The subsequent resuspension of highly radioactive Cs particles has been suggested as a possible reason for the delay in radioactive Cs depuration from benthic biota. Highlights: We observed radioactive Cs concentrations of suspended matter around the FDNPP. The 134 Cs concentrations ranged from 279 to 678 Bq kg −1 . The 137 Cs concentrations ranged from 893 to 2079 Bq kg −1 . We discovered highly radioactive Cs particles from suspended matter. A contribution ratio of these particles to each samples were 36% on average.